The impact of structural transformation on global value chains in the MENA countries - Nihel Frikha; Foued Badr Gabsi (Naše gospodarstvo / Our Economy, 2024)
Several studies on economic transition propose that structural change in developing countries, that involves reallocating from less productive to more productive sectors, might enhance participation in global value chains (GVCs). However, there is a lack of empirical work on this claim. This study explores the factors affecting global value chain (GVC) participation in the Middle East and North Africa (MENA) region while considering structural transformation from 2000 to 2018. By applying the system GMM empirical research method, we found that structural change significantly contributes to facilitating the position of MENA economies under consideration. Specifically, the service and industry sectors play pivotal roles in these countries. This study also postulates that if we want to strengthen the participation of companies in GVCs, access to the internet, and a high level of education tertiary are necessary Also, environment and policies conducive to investment and direct investment abroad are important. The study posits positive commercial and financial links, and population size as important factors in promoting this position.
Keywords: F02; F14; L16; O14; 330; Global Value Chains; GMM; MENA countries; Structural transformation